Hemochromatosis gene mutations, liver function tests and iron status in alcohol-dependent patients admitted for detoxification - Robinson, Geoffrey; Narasimhan, Seshasayee; Weatherall, Mark; Beasley, Richard (Journal of gastroenterology and hepatology, 2007)
Background:  Screening of target populations for hemochromatosis (HFE) gene allele status has been recommended. Alcoholic liver disease may be associated with iron overload and there is evidence of excessive alcohol consumption among patients with hereditary hemochromatosis. This study determined the HFE gene allele status in alcohol‐dependent patients and explored the associations between iron status, liver enzymes, and HFE status. Methods:  A total of 151 consecutive patients admitted for alcohol detoxification were tested for HFE mutations, iron status, and liver function tests. The prevalence data were compared with those from a New Zealand population. manova was used to compare liver function tests and iron status for subjects with different HFE mutations. Results:  Three compound heterozygotes, one homozygote for C282Y, and one homozygote for H63D were found among the 151 patients. For the remaining 146 patients, there was no difference in the distribution of heterozygote status by allele, compared to the general New Zealand population. No HFE mutation: general population 64.4%, alcohol‐dependent patients 64.4%; H63D: general population 23.6%, alcohol‐dependent patients 28.1%; C282Y: general population 11.9%, alcohol‐dependent patients 7.5% (P = 0.20). There was no relationship between liver function tests or iron status and HFE mutation status among the study group. Conclusions:  No evidence has been found in the present that HFE allele status prevalence is different from the general population or associated with different liver function or iron status among alcohol‐dependent patients. The cause of altered iron status among alcohol‐dependent patients does not appear to be related to HFE status.